Comparative Analysis of Compulsory Heirship Independent of Will Content in Vietnamese and French Law: Key Differences and Proposals for Enhancing Vietnamese Regulations - Do, Cong Nam; Nguyen, Duy Dzung (Український політико-правовий дискурс, 2025)
Purpose of this study aims to clarify the basis for determining individuals entitled to the compulsory portion of the estate independent of the will's content under Vietnamese and French law, through analysis and comparison of relevant provisions. Specifically, the article focuses on protecting the rights of vulnerable family members, while proposing recommendations to improve Vietnamese law to better align with modern social realities, balancing the testator's freedom to dispose of property and family moral obligations. This stems from the observation that Vietnam's current regulations are narrow in scope, not covering common cases such as adopted children, economically dependent persons, or long-term caregivers, whereas French law has a more flexible mechanism, profoundly influencing Vietnam's civil system. Method of the article employs a comparative legal method, focusing on analyzing Article 644 of the Vietnamese Civil Code 2015 and Articles 912-930 of the French Civil Code. Contents are contrasted by each group of subjects (parents, children, spouse, and fetus), including provisions on intestate and testate succession. Additionally, the research references practical cases (such as the Johnny Hallyday case in France), reference materials, and recent legal reforms (such as the 2007 amendment in France removing parents from compulsory heirs). Based on differences, the article proposes improvement recommendations, combined with sociological analysis to ensure feasibility and humanity. Results The comparative results show that both systems aim to protect vulnerable family members, but the scope and mechanisms differ markedly. Vietnamese law specifies four groups entitled to the compulsory portion (minor children or adult children without labor capacity, parents, spouse), emphasizing blood ties and legal nurturing relationships, but lacks flexibility and does not cover legally adopted children, economically dependent persons, or actual caregiving relationships. In contrast, French law focuses on protecting children (réserve héréditaire occupying a large ratio depending on the number of children), prioritizes the spouse with lifetime usufruct rights, and eliminated parents from compulsory heirs since 2007 to enhance the testator's dispositive rights. For the fetus, France applies the principle beneficial to the child, while Vietnam emphasizes proof conditions (conceived before death, alive for at least 24 hours after birth). The differences reflect France's orientation towards nuclear families and greater flexibility, while Vietnam maintains tradition but is not suited to diverse modern family relationships. From this, the study proposes expanding subjects in Vietnam: adding legally adopted children, economically dependent persons, long-term caregivers; flexibly adjusting compulsory ratios based on economic conditions; and perfecting mechanisms for managing the fetus's estate portion (temporary suspension of division, appointment of manager). Conclusion Improving Vietnamese law by expanding the scope of compulsory heirs will contribute to ensuring fairness, humanity, and alignment with social realities, reducing family disputes and harmonizing individual rights with moral obligations. The recommendations not only draw from French experience but also need to integrate with Vietnam's cultural context, through amending Article 644 of the Civil Code and issuing detailed guidelines on proving relationships, temporary estate management, to better protect vulnerable subjects without weakening the freedom to dispose of property.